PENGARUH MODEL PEMBELAJARAN EARTHCOMM PADA MATA PELAJARAN GEOGRAFI TERHADAP KEMAMPUAN BERPIKIR SPASIAL SISWA DI SMA NEGERI 2 KOTA KUPANG - Tibhi, Maria Vatima; Wulakada, Hamza Huri; Sunimbar, Sunimbar (Universitas Nusa Cendana, 2024)
Earth Science System In The Community Learning Model is a model that is oriented towards problems that occur in the earth that can be solved within the scope of the community (society). The purpose of this study was to determine the effect of the Earth Science Community (EarthComm) learning model i n geography subjects on students' spatial thinking skills at SMA Negeri 2 Kota Kupang. The type of research used is quantitative research, the method used is quasi-experimental with the form of research design is Nonequivalent Control Group Design. The population of this study is all students of class XI IPS with sampling techniques using saturated sampling techniques. The results of this study indicate that the average value of the experimental class is higher than the control class. It is known that the average value of the control class is 69.57 and the experimental class is 75.86 so that there is a difference between the two. Based on the results of data analysis of the Independent Sample T-Test test, there is an effect of the Earth Science System in the Community (EarthComm) learning model in geography subjects on students' spatial thinking skills compared to the control class using the conventional model. The EarthComm learning model is recommended to be used as a variation of teacher learning in the application of the learning model. This model can also be develo ped by other researchers by adding moderator variables or other media.